Alexander the Great's invasion of the East and its effects on Kurdistan and Iran - حەمەشیرین, دڵگەش ئیبراهیم (Sulaimani Journal for Humanities, 2019)
The main purpose of this study is to address the issue of historical writers at various stages The east in general and Kurdistan and Iran in particular were the targets of the invasion. As a result There have been several battles since the beginning of the campaign, such as the Battle of Granicus, Isos, in Asia Small also the famous battle of Guagam, known in some sources as Arbek It is considered to be the unifier between the Greeks and the Achaemenid Empire Erbil. This war brought an end to the Achaemenid Empire, the largest empire in the world It was ancient, ruling most of the ancient world for more than two centuries. In this study, we have discussed several attacks on the East in general and Kurdistan and Iran in particular There were reasons, they became the heroes of this war we have determined. The changes that have occurred in Kurdistan and Iran as a result of this campaign presented to us. Although it has a lot of positive and negative effects for we have problems in many aspects clearly color gave back in later times. These influences are social, political, economic, social and intellectual We have discussed in detail in the study. We also have several sources in this study Kurdish, Arabic, Persian, Greek are enough to do a completely scientific work, I hope This place of work should fill the gap in the history of Kurdistan and Iran at this stage.